Based on optimally rigid graph energy efficient distributed topology control algorithm - Xiao-yuan LUO; Yan-lin YAN; Li-juan HAO; Shao-bao LI; Xin-ping GUAN (Tongxin xuebao)
To solve the problem that most of existing algorithms cannot balance energy consumption,the energy efficient distributed topology control algorithm (OREE) based on optimally rigid graph was presented.Through the link weight function reflecting both the energy consumption and residual energy of two end nodes,OREE builds a dynamic network topology that changes with the variation of node energy,and thus balances energy consumption of nodes.The topology derived under OREE is 2-connected and sparse was proved,and the average degree of nodes in the topology converges to four approximately.Furthermore,simulation results show that OREE can balance energy consumption of nodes effi-ciently compared with other algorithms,thereby extend the lifetime of networks.